Computational Docking-Based Evaluation of Novel β-Lactam Analogues Against Treponema pallidum via RhoGTPase-Activating Protein (1RT2) Inhibition for Enhanced Antisyphilitic Activity - Thakare, Vinod Madhaorao; Verma, Bhawani Shankar; Rani, Khushboo; Mishra, Sanjay; Singh, Sumita; Gupta, Prem Shankar; Goyal, Anjali; Syed, Manjoor Ahamad (Journal of Neonatal Surgery, 2025)
Syphilis, caused by the spirochete Treponema pallidum, remains a globally resurgent sexually transmitted infection with significant public health implications. Despite the proven efficacy of Penicillin G, emerging therapeutic challenges such as patient hypersensitivity, pharmacokinetic limitations in neurosyphilis, and resistance trends in related bacterial species necessitate the identification of novel or optimized β-lactam analogues. This study employed a structure-based drug design approach to evaluate the binding affinity and molecular interactions of five β-lactam derivatives Penicillin G, Penicillin V, Ampicillin, Amoxicillin, and Methicillin against RhoGTPase-activating protein (PDB ID: 1RT2), a surrogate target relevant to the regulation of host-pathogen cytoskeletal signaling. Molecular docking simulations were performed using AutoDock Vina and PyRx, and interaction analyses were visualized using Chimera and LigPlot+. Penicillin G exhibited the most favorable docking score (–9.1 kcal/mol), forming strong hydrogen bonds and π–π stacking with active site residues such as TYR181, TRP229, and GLN64, indicating a highly stable ligand–receptor complex. Comparative analysis revealed that increased steric bulk and polar substitutions in other analogues hindered optimal binding. Structure–activity relationship (SAR) findings suggest that minimal side chain substitutions and hydrophobic compatibility significantly enhance 1RT2 binding. These results highlight Penicillin G as a potent RhoGTPase pathway modulator and reinforce its superiority among β-lactam analogues for antisyphilitic therapy. Furthermore, this docking-based study provides mechanistic insights for the rational design of next-generation spirocheticidal agents targeting regulatory protein systems.